2021
DOI: 10.1029/2020jc016922
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 3‐Dimensional Structure and Heat Budget of Mesoscale Eddies in the South Atlantic Ocean

Abstract: Mesoscale phenomena such as mesoscale eddies, with typical spatial scales of 50-300 km and temporal scales ranging from weeks to months, are prevalent in the world oceans. They carry huge kinetic ener-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
(152 reference statements)
2
8
0
Order By: Relevance
“…Both Wang et al. (2021) and Dawson et al. (2018) showed dipole eddies north of the ACC and monopole eddies within the ACC, yet our results show that both monopole and dipole structures can occur in eddies of similar size and geographic distributions (see CE Nodes 2 and 4 in Figure 3b and Figures S6 and S9 in Supporting Information ).…”
Section: Discussionsupporting
confidence: 40%
See 3 more Smart Citations
“…Both Wang et al. (2021) and Dawson et al. (2018) showed dipole eddies north of the ACC and monopole eddies within the ACC, yet our results show that both monopole and dipole structures can occur in eddies of similar size and geographic distributions (see CE Nodes 2 and 4 in Figure 3b and Figures S6 and S9 in Supporting Information ).…”
Section: Discussionsupporting
confidence: 40%
“…Both Wang et al (2021) and Dawson et al (2018) showed dipole eddies north of the ACC and monopole eddies within the ACC, yet our results show that both monopole and dipole structures can occur in eddies of similar size and geographic distributions (see CE Nodes 2 and 4 in Figure 3b and Figures S6 and S9 in Supporting Information S1). Variations in spatial tracer distributions point to the possibility of different dominant mechanisms at play within differently-orientated eddy nodes, which could be linked to seasonal or life stage characteristics.…”
Section: Deconstructing the Influence Of Diverse Mesoscale Eddy Types...mentioning
confidence: 67%
See 2 more Smart Citations
“…The heat and salt fluxes due to eddies have been recognized as one of the fundamental mechanisms for the oceanic meridional heat and salt transport (Dong et al., 2014; Meijers et al., 2007; Sun, Liu, & Wang, 2019; Treguier et al., 2014; Wang et al., 2023). Although many studies have been conducted on the heat transport by eddies in the ocean, relatively little attention has been directed toward the transport of salt by eddies, especially at a global scale (Chen et al., 2012; Jayne & Marotzke, 2002; Sun et al, 2018; Sun, Liu, & Wang, 2019; Volkov et al., 2008; Wang et al., 2021; Zhang et al., 2014). Based on eddy‐resolving model simulations, studies estimate meridional eddy salt transport based on the product of temporal velocity and salinity anomalies, represented as trueV'S' $\overline{V{\rhook}S{\rhook}}$ (Meijers et al., 2007; Treguier et al., 2014).…”
Section: Introductionmentioning
confidence: 99%